A compact wideband balun design using double‐sided parallel strip lines with over 9:1 bandwidth. Issue 11 (5th September 2020) - Tamjid, Farshid; Thomas, Chris M.; Fathy, Aly E.
Abstract: A simplified miniaturized wideband balun design covering (0.38‐3.5 GHz) is presented. The broadband balun structure occupies a small area of 20.7 mm × 20.8 mm. The balun is designed using low loss double‐sided parallel strip lines and is comprised of a two‐stage Wilkinson divider followed by loading, symmetrically, the two output ports. One port with a phase inverter circuit; while a very similar but non‐inverting circuit is placed in the other port for loading‐balance compensation. To realize the balun's function, different smooth transitions have been employed and were accounted for. The fabricated balun circuit demonstrated phase and amplitude imbalance of less than ±5° and ± 0.4 dB, respectively, over the band.